Implementation Of National Defense Values In Strengthening The National Defense Legal System In Indonesia - Satino Satino; Ilona Vicenovie Oisina Situmeang (LPPM Universitas PGRI Sumatera Barat, 2025)
National defense is the right and obligation of every citizen who has a strategic role in maintaining the sovereignty and integrity of the Unitary State of the Republic of Indonesia. This study aims to analyze the implementation of national defense values in strengthening the national defense legal system in Indonesia. Defense and national defense regulations in Indonesia are based on the 1945 Constitution Article 27 paragraphs (3) and 30, and Law Number 3 of 2002 concerning National Defense. This emphasizes the rights and obligations of citizens in defense through the total people's defense system, technically regulated by the Minister of Defense Regulation Number 8 of 2022 concerning the Development of National Defense Awareness. The method used is normative legal research with a statutory and conceptual approach. The results of the study indicate that the implementation of national defense is still normative and has not been optimally integrated into the defense legal system. In addition, there are various obstacles such as weak public legal awareness and unsynchronized regulations. Therefore, a strengthening strategy is needed through national defense education, regulatory harmonization, and increasing the role of society in the national defense system